Public safety networks from LTE to 5G - Yarali, Abdulrahman (John Wiley & Sons, 2020)
"The public safety community has undergone significant strides towards strengthening its abilities, capacity and improving the communications of emergencies. Public safety depends on fast and efficient levels of communication in order to properly relay time-sensitive and critical pieces of information The first responders, however, are still limited due to the presence of the fragmented networks and use of decade-old technologies in public safety agencies. They are using LMR for a majority of their communications and as an outcome, public security has struggled to speak across jurisdictional and company lines This book will discuss the evolution of the public safety system requirements by providing a technical analysis of the existing public safety network, 4G LTE and its applications in public safety and security, a comprehensive analysis of 5G-network technology, the link between the most recent application of 4G and 5G, efficient utilization and the spectrum sharing for public safety communications systems"--